State of the Art and Perspectives of Inorganic Photovoltaics. (11th June 2013) - Le Donne, A.; Scaccabarozzi, A.; Tombolato, S.; Marchionna, S.; Garattini, P.; Vodopivec, B.; Acciarri, M.; Binetti, S.
Abstract : In the last decade, the fast increase of the global energy consumption, mainly related to the strong economic growth in the Far East, and the progressive depletion of the fossil fuels induced a run-up in the world oil price. Both these economic concerns and the growing global pollution pointed out that a transition toward renewable energies is mandatory. Among renewables, the conversion of sunlight into electricity by photovoltaic (PV) devices is a reliable choice to cope the growing energy consumption, due to the huge potentially extractable power (up to 120000 TW). The most important classes of inorganic PV devices developed in the last sixty years will be reviewed in this paper, in order to depict the state of the art of the technologies which dominate the PV market. Some novel concepts which could have an important role in the future of PV will be also described.